The analysis of the deformation of single node in a modular scaffolding system - Pieńko, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The increasingly complex engineering structures of scaffoldings require optimal designing in terms of safety, economy and erection. This approach requires detailed knowledge of the static-strength properties of elements, as well as knowledge of their interconnections. The paper deals with the laboratory tests of deformations in modular scaffolding nodes for the following loads: torque of the ledger, shearing and bending in the horizontal plane. The original grip was used in the study, which allows to load the node with aforementioned loads. The result of research is a description of the deformation of the nodes and the load-displacement graphs. The studies presented in the paper indicate that graphs are repeatable, which is not obvious in the case of nodes assembled manually. This means that it can be used as a basis for the verification of non-linear numerical analysis, which will have to take into account such issues as the material nonlinearities, geometric nonlinearities, contact and friction.